1990
DOI: 10.1136/jcp.43.3.262-a
|View full text |Cite
|
Sign up to set email alerts
|

Serum IgE concentrations in complete Behçet's disease.

Abstract: Kim YS. Expression of a carbohydrate differentiation antigen, stage specific embryonic antigen, in human colonic adenocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that the IGL locus or genes polymorphisms are associated with autoimmune disorders 38 39. In addition, an association between BD and elevations of some immunoglobulins has been noted 40–43…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the IGL locus or genes polymorphisms are associated with autoimmune disorders 38 39. In addition, an association between BD and elevations of some immunoglobulins has been noted 40–43…”
Section: Discussionmentioning
confidence: 99%
“…14 Likewise, Cengiz reported that the serum IgE concentrations were greater patients with Behcet's disease than those in controls, and the serum IgE levels were positively correlated with disease duration. 15 In our study of 128 patients with acute VKH disease, 27.34% had elevated serum IgE levels. Despite similar age at onset and time from symptom onset to diagnosis, patients with elevated serum IgE levels had worse visual acuity, suggesting that elevated serum IgE may be associated with more severe acute VKH disease.…”
Section: Discussionmentioning
confidence: 58%
“…Cengiz reported that sT IgE concentrations were significantly higher in patients with BD than in the control group. He pointed out that there was a positive correlation between serum IgE concentrations and the duration of the disease 14 . Dinc et al .…”
Section: Discussionmentioning
confidence: 99%